DNA barcode de drosofilídeos micófagos pertencentes aos gêneros Hirtodrosophila, Mycodrosophila e Zygothrica - Bolzan, Andreza Ribeiro (2011)
The biodiversity that exists in our planet is huge and far from being known. Most of the times the techniques that are used in species identification are based in the morphology of the specimens, and the description is a time-consuming work, that is limited to specialists. At contrast, DNA Barcode is intended to be a fast and accessible tool, which proposes the use of a standard DNA sequence encompassing the mitochondrial cytochrome c oxidase subunit I (COI) gene, with the aim of identifying species from already described sequences and discovering new species. Nevertheless, its efficiency is based on the diagnosis of specific properties, as monophyly of the intraspecific sequences and the existence of a Barcode gap between intra and interspecific variation. In this study, we tested the efficacy of the DNA Barcode in the identification/discovery of mycophagous drosofilid species belonging to the genera Hirtodrosophila, Mycodrosophila and Zygothrica. The specimens were collected throughout the southern Brazil, specially in the Santa Catarina and Rio Grande do Sul states, which totalized 10 collection points and 177 individuals. After morphological identification, total DNA was extracted and the COI (cytochrome oxidase c subunit I) and COII (cytochrome oxidase c subunit II genes) were amplified and sequenced, holding a total of 117 and 137 sequences, respectively, which were analyzed through phenetic and phylogenetic methods. A total of 33 different morphotypes were encountered and, with the collections it was possible to realize that the mycophagous genera Hirtodrosophila, Mycodrosophila and Zygothrica are well distributed throughout the Southern Brazilian Region. Furthermore, many species have here their first description for the sampled region. The molecular analyses revealed the existence of a Barcode gap between the intra and the interspecific distances, although there was an overlap between the interespecific congeneric and intergeneric variation, prperties which hamper clear generic delimitation but stimulate DNA Barcode utilization for species designation. The phenograms/phylogenies obtained through the algorithms of Neighbor- Joining/Bayesian Inference also have shown that despite the reciprocal monophyly presented by the different species, the three genera were shown as polyphyletic within Drosophilidae. In this sense, we suggest here that the DNA Barcode technique is effective in the mycophagous species discrimination, but not in genera differentiation. In fact, the application of this technology for this group of species revealed straightforward utility in cryptic species discrimination when the analysis of morphological characters is not precise, mainly due to the exclusive existence of females. Moreover, our data show the importance of joining DNA Barcode with morphological data, which may help in the delimitation or even in the differentiation of likely new species.